2014
DOI: 10.1111/sltb.12076
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Cognitive Reappraisal and Expressive Suppression to Suicidal Ideation and Suicidal Desire

Abstract: The differential relations between the emotion regulation strategies "cognitive reappraisal" and "expressive suppression" and suicidality in a mixed inpatient sample (N = 232, 69.4% female) of a German psychotherapeutic hospital were examined. Patients filled in the Emotion Regulation Questionnaire and items on suicidal ideation and desire. A structural equation model fitted the data (RMSEA = .044; CFI = .96) and revealed that "expressive suppression" significantly predicted increased suicidal ideation. Modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
32
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 51 publications
(69 reference statements)
11
32
2
Order By: Relevance
“…Yet, we did not observe a relation between cognitive reappraisal and suicidal thoughts. This is consistent with prior work by Forkmannc () who did not find a significant association between cognitive reappraisal and suicidality. Cognitive reappraisal alters the semantic and perceptual representations of stimuli that evoke emotions (Buhle et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Yet, we did not observe a relation between cognitive reappraisal and suicidal thoughts. This is consistent with prior work by Forkmannc () who did not find a significant association between cognitive reappraisal and suicidality. Cognitive reappraisal alters the semantic and perceptual representations of stimuli that evoke emotions (Buhle et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that individuals who habitually use expressive suppression as an emotion regulation strategy and who happen to endorse disordered eating attitudes and behaviors are also more likely to experience suicidal thoughts with increased frequency. This report extends past research by Forkmann et al () who observed that expressive suppression predicted suicidal ideation in a mixed‐gender inpatient sample. Overall, our data suggest that the use of maladaptive strategies to regulate emotional experiences could enhance the relationship between disordered eating and suicidal behaviors.…”
Section: Discussionsupporting
confidence: 89%
“…As previously mentioned, reappraisal is one of the most widely studied approaches to volitionally modulate affect (Ochsner & Gross, 2005); however, there are other strategies available. For instance, expressive suppression is another form of emotion regulation that is associated with poor physical and psychosocial outcomes (Butler et al, 2003; Forkmann et al, 2014). To examine individual differences in typical emotion regulation strategy use, participants completed the Emotion Regulation Questionnaire (ERQ; Gross & John, 2003), which provides separate indices of the tendency to use cognitive reappraisal and expressive suppression when regulating emotions.…”
Section: Introductionmentioning
confidence: 99%
“…A community sample of 118 undergraduate students demonstrated that effortful suppression was significantly associated with suicidal ideation (51), and a recent study of 627 undergraduates found that ER deficits moderated the association between ADHD and suicidal ideation (52). This appears to hold true through the life cycle, as suppression was significantly associated with suicidal ideation among a sample of 232 adults on an inpatient unit, even after controlling for a current depressive episode (53).…”
Section: Epidemiological Evidence Directly Connecting Er and Suicide mentioning
confidence: 96%